DRIP IRRIGATION AUTOMATION WITH A WATER LEVEL SENSING SYSTEM IN A GREENHOUSE - M. Yıldırım (Journal of Animal and Plant Sciences, 2016)
Automated control systems in irrigation have in recent years made considerable progress, offering a wide range of new options. In this experiment, drip irrigation system automatically governed irrigation in accordance with a water level sensing system in the mini-pan with the help of evaporation. Data acquisition was performed by an electronic circuit, which processed data and then sent the data to the microcontroller (Pic16f877). In the system, a closed loop control system based on sensing water level in the mini-pan was used to activate irrigation, thereby the system started irrigation whenever water level in the mini-pan dropped to the set level. The performance of the automated system can be increased as the irrigation timing in the software is adjusted according to plant growth stages.
Keywords: automated irrigation; drip irrigation; water level sensor; irrigation controller; mini-pan